2011 Review of Conditionality : Overview Paper. (Policy Papers; Policy Paper ;, 2012)
The review generally yields positive findings on conditionality and design in Fund-supported programs. Programs in the review period internalized lessons from the past, for example with program design incorporating the lessons of the Asian crisis, and the approach to conditionality being modified to take into account the recommendations made in the 2007 report on structural conditionality by the Fund's Independent Evaluation Office (IEO). (Box 1 also summarizes recommendations from the previous Review of Conditionality and follow-up.) These findings hold for the substantial majority of programs supported under both the Fund's General Resources Account and the Poverty Reduction and Growth Trust (hereafter GRA programs and PRGT programs, respectively).